Patrimônio histórico-cultural: critérios para tombamento de bibliotecas pelo IPHAN - Murguia, Eduardo Ismael [UNESP]; Yassuda, Silvia Nathaly [UNESP] (Escola de Ciência da Informação da UFMG, 2007)
Em razão do conteúdo informacional que preservam, as bibliotecas são consideradas grandes centros de memória. Tal fato motivou uma análise das bibliotecas tombadas pelo Iphan, com os seguintes objetivos: iniciar uma reflexão sobre suas peculiaridades enquanto patrimônio histórico-cultural, conhecer as justificativas oficiais que levaram ao tombamento, e discriminar o tombamento do prédio e/ou da coleção. Detectou-se que apenas o monumento arquitetônico das bibliotecas foi o critério priorizado, e que o tombamento delas foi apenas conseqüência do tombamento do edifício que as abrigava.

Because of the information content that they hold libraries are considered important centers of memory. Thus, in order to start a reflection on the peculiarities of libraries as a cultural heritage an analysis of libraries listed by IPHAN was undertaken. Also, we attempted to recognize the official justifications that lead the buildings or the collections to be listed. Questionnaires were sent and applied. It was detected that the criteria for the listing process were primarily historical and architectural values, and the collection was listed as a consequence.
Historical-cultural heritage: criteria for libraries listed by IPHAN
Keywords: Patrimônio Histórico; Biblioteca; Coleções de Obras Raras; Historical Heritage; Library; Special Collections